طرابلس الغرب في فترة فرسان القديس يوحنا(1530م-1551م) - هيام مساعدي (My University, 2025)
Summary in English: This study addresses the history of the city of Tripoli in the West, which enjoys a strategic geographical location that attracted the ambitions of European powers. It was occupied by the Spaniards in 1510, but they faced difficulties in controlling it. Emperor Charles V handed it over to the Knights of St. John in 1530. During their rule, the city experienced continuous unrest and conflicts. Despite their attempts to impose their authority, the weakness of the fortifications and the scarcity of resources weakened their position. They imposed high taxes and a strict regime, which angered the locals who tried to expel them without success. As the situation worsened, the locals sought assistance from the Ottoman Sultan Suleiman the Magnificent, who sent a fleet led by Sinan Pasha and Dragut, and managed to capture the city after a week-long siege in 1551. This marked the beginning of the Ottoman era with the appointment of Murad Agha as governor. -------------------------------- الملخص باللغة العربية: تعالج هذه الدراسة تاريخ مدينة طرابلس الغرب، التي تتمتع بموقع جغرافي استراتيجي جذب أطماع القوى الأوروبية. احتلها الإسبان عام 1510م، لكنهم واجهوا صعوبات في السيطرة عليها، فقام الإمبراطور شارل الخامس بتسليمها لفرسان القديس يوحنا عام 1530م. خلال حكم هؤلاء الفرسان، شهدت المدينة اضطرابات وصراعات مستمرة. ورغم محاولاتهم فرض سلطتهم، أدى ضعف التحصينات وقلة الموارد إلى فشلهم، ففرضوا ضرائب مرتفعة ونظامًا صارمًا، مما أثار استياء الأهالي الذين حاولوا طردهم بلا جدوى. مع تفاقم الوضع، طلب الأهالي مساعدة السلطان العثماني سليمان القانوني، فأرسل أسطولًا بقيادة سنان باشا ودرغوث رئيس، وتمكنوا من استعادة المدينة بعد حصار دام أسبوعًا في عام 1551م، ليبدأ بعدها العهد العثماني بتعيين مراد أغا والياً عليها. -------------------------------- Résumé en français : Cette étude traite de l’histoire de la ville de Tripoli de l’Ouest, qui bénéficie d’une position géographique stratégique qui a attiré les convoitises des puissances européennes. Elle fut occupée par les Espagnols en 1510, mais ces derniers rencontrèrent des difficultés à la contrôler. L'empereur Charles Quint la remit alors aux Chevaliers de Saint-Jean en 1530. Pendant leur règne, la ville a connu des troubles et des conflits incessants. Malgré leurs tentatives d'imposer leur autorité, la faiblesse des fortifications et le manque de ressources ont affaibli leur position. Ils ont donc imposé des taxes élevées et un système strict, ce qui a suscité l'hostilité des habitants qui ont tenté de les expulser en vain. Face à l’aggravation de la situation, les habitants ont demandé l'aide du sultan ottoman Soliman le Magnifique, qui envoya une flotte sous le commandement de Sinan Pacha et Dragut, permettant ainsi la reconquête de la ville après un siège de semaine en 1551. Cela a marqué le début de l'ère ottomane avec la nomination de Murad Agha comme gouverneur.
Keywords: طرابلس الغرب، الإحتلال الإسباني، فرسان القديس يوحنا، السلطان العثماني